Physical and Functional Analysis of the Putative Rpn13 Inhibitor RA190 - Dickson, Paige (Cell Chem Biol, 2020)
Rpn13 is one of several ubiquitin receptors in the 26S proteasome. Cys88 of Rpn13 has been proposed to be the principal target of RA190, an electrophilic small molecule with interesting anti-cancer activities. Here, we examine the claim that RA190 mediates its cytotoxic effects through engagement with Rpn13. We find no evidence that this is the case. In vitro, RA190 is has no measurable effect on any of the known interactions of Rpn13. In cellulo, we see no physical engagement of Rpn13 by RA190, either on C88 or any other residue. However, chemical proteomics experiments in two different cell lines reveal that dozens of other proteins are heavily engaged by RA190. Finally, increasing or reducing the level of Rpn13 in HeLa and melanoma cells had no effect on the sensitivity of HeLa or melanoma cells to RA190. We conclude that Rpn13 is not the physiologically relevant target of RA190.